AKTIVITAS ANTIINFLAMASII EKSTRAK ETANOL BATANG WOLE WOE PADA TIKUS DENGAN METODE RAT HIND PAW EDEMA - Safriani Rahman; Sitti Amirah; Fitriana Fitriana; Bayu Putra (Fakultas Farmasi UMI, 2023)
Inflammation is the natural protective response of the body to tissue damage brought on by toxic chemicals, microbiological organisms, or physical trauma. The purpose of this investigation is to find out how active the ethanol extract of Wole woe stem is and how much of it is needed to get results. This anti-inflammatory study was conducted on 15 rats using the rat hind paw edema method. The rats were divided into 5 groups: group I served as a negative control (Na.CMC), group II served as a positive control (diclofenac sodium 0.9 mg/kgBW), groups III, IV, V received doses of Wole woe stem ethanol extract ranging from 100 mg/kgBW to 400 mg/kgBW, respectively. Oral administration was used for all the test materials, and after an hour, each test animal received a subplantar injection of 0.1 milliliters of 1% carrageenan solution. A plethysmometer was used to take readings every hour for a period of eight hours to get an accurate reading of the volume of the rat’s foot. The collected test results were subjected to statistical analysis, in which a one-way ANOVA and a post hoc LSD test were used. According to the findings of the research that was carried out, it was discovered that an ethanol extract of Wole woe stems possessed anti-inflammatory action, and the most effective dose was found to be 400 milligrams per kilogram of body weight (mg/kgBW).